Inside Back Cover: An Evolutionary Model Encompassing Substrate Specificity and Reactivity of Type I Polyketide Synthase Thioesterases (ChemBioChem 18/2014). Issue 18 (15th December 2014) - Hari, Taylor P. A.; Labana, Puneet; Boileau, Meaghan; Boddy, Christopher N.
<x xml:space="preserve">Abstract</x> The inside back cover picture shows multiple chemistries including macrodiolide formation accessible from thioesterases (TEs) presented with an unnatural substrate. Phylogenetic analysis by C. N. Boddy et al. (p. 2656 ff.) supports a convergent evolutionary model for macrodiolide‐forming TEs. The work suggests TEs are by nature non‐selective for the type of chemistry they catalyze and can produce a range of metabolites.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>